Tools and techniques for financial stability analysis - Ramlall, Indranarain (The theory and practice of financial stability ;, 2018)
Combatting financial stability risks is a highly challenging task which can by no means be concentrated into a 'one-size fits all' approach. It is important to select the appropriate tools and techniques in order to monitor, analyse, and maintain financial stability through proactive policy measures. 'Tools and Techniques for Financial Stability Analysis' explores all key aspects of analytical tools and challenges for sound financial stability assessments. Comprehensive coverage is given to value at risk, stress testing, graphical tools for financial stability, the financial system stress index, as well as ratios and metrics of financial stability assessment. Finally, a concluding chapter is devoted to understand the key challenges involved in maintaining financial stability. This book will prove valuable to central bankers, economists, and policy-makers who are involved in the field of financial stability, as well as researchers studying the field.